2018
DOI: 10.25299/jeee.2018.vol7(2).2215
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Imbibition Test of Low Salinity Injection at Low Saline Waxy Crude Carbonate

Abstract: Low salinity waterflooding (LSW) is categorized as one of emerging EOR technologies. It is done by injecting water with different salt composition and/or concentration. The research has been carried out for both sandstone and carbonate with the results looks promising. However, most of this research still concentrated in the north sea, middle east and North America region. This article discusses the applicability of low salinity waterflooding methodology in Indonesia. Spontaneous imbibition test is carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…As well as salinity, the ionic composition of the injected water may play a significant role in increasing oil recovery. CaCl 2 and NaCl solutions were prepared, for example, when studying low-salt waterflooding on core (Lie Yang et al 2016;Al-Obaidi 2021;Hidayat, Erfando & Maulana 2018). Having the same salinity of 5000 mg/l, the sodium solution increased the oil recovery factor by 7% more than the calcium solution.…”
Section: Criteria For Low-salt Floodingmentioning
confidence: 99%
“…As well as salinity, the ionic composition of the injected water may play a significant role in increasing oil recovery. CaCl 2 and NaCl solutions were prepared, for example, when studying low-salt waterflooding on core (Lie Yang et al 2016;Al-Obaidi 2021;Hidayat, Erfando & Maulana 2018). Having the same salinity of 5000 mg/l, the sodium solution increased the oil recovery factor by 7% more than the calcium solution.…”
Section: Criteria For Low-salt Floodingmentioning
confidence: 99%
“…Song explained that the change in 2 of 12 wettability was caused by less Na+ surface complexes in low-salinity water by calculating the electrostatic component of the separation pressure [10]. Experiments by Hidayat found that brine solutions containing high Mg 2+ and Ca 2+ significantly improved the recovery efficiency of osmotic water [11]. The explanation for this phenomenon by Ghandi et al is that the brine solution containing divalent ions such as Mg 2+ and Ca 2+ can change the wettability of lipophilic rocks to low lipophilic or neutral wettability, thereby improving the imbibition recovery [12].…”
Section: Introductionmentioning
confidence: 99%